2009
DOI: 10.1109/tap.2009.2029308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential Biological Effects of the 60-GHz Millimeter Waves Upon Human Cells

Abstract: International audienceWe investigate potential biological effects of low-power millimeter-wave radiation on human cell viability and intracellular protein homeostasis. A specific exposure system allowing to perform far-field exposures with power densities close to those expected from the future wireless communications in the 60-GHz band has been developed and characterized. Specific absorption rate (SAR) values were determined for the biosamples under test using the FDTD method. It was shown that millimeter-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…We reported that levels of several stressinducible genes were not significantly enhanced [29,32], suggesting that MMW around 60…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We reported that levels of several stressinducible genes were not significantly enhanced [29,32], suggesting that MMW around 60…”
Section: Discussionmentioning
confidence: 89%
“…It includes a signal generation subunit and an exposure chamber. The first subunit had already been described in detail [29]. The anechoic exposure chamber is located in a temperaturecontrolled anechoic MEMMERT UNE400 incubator (Memmert GmbH, Schwabach, DE) covered inside by absorbing materials.…”
Section: Exposure System Dosimetry and Experimental Setupmentioning
confidence: 99%
“…However, these results have not been reproduced, and other studies have showed that neither the cell doubling time nor the cell cycle is significantly modified by MMW exposure [Beneduci, 2009;Zhadobov et al, 2009]. At the molecular level, 60 GHz radiation below 1 mW/cm 2 can induce structural modifications in artificial biomembranes [Zhadobov et al, 2006].…”
Section: Mmw At Intermediate Pd (5-15 Mw/cmmentioning
confidence: 91%
“…The six-well tissue culture plate (8.5 cm  12.7 cm) containing the cells was placed in the MEMMERT UE400 incubator (Fisher Scientific, Illkirch, France) at 37 8C and irradiated from the bottom by a pyramidal horn antenna. The main units and characteristics of this exposure set-up were previously described in detail [Zhadobov et al, 2009]. Sham exposures were performed under the same experimental conditions but with the generator switched off.…”
Section: Exposure Set-up and Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation